Socialization of Making Salted Eggs with Water Media to Improve the Soft Skills of the Residents of Pindrikan Lor Semarang - Istianah; Mudjiastuti Handajani; Adolf Situmorang; Yayan Adi Saputro (Indonesian Journal of Society Development, 2023)
Eggs are an almost perfect source of animal protein. Consumption of chicken eggs is a perfect food ingredient that contains high nutrients. Increasing the consumption of salted eggs can be done by making salted eggs in a wet way. In using wet media it is very easy to use water media which can be measured with certainty in adjusting the amount of salt content added. Salt levels are very influential in the results of these eggs later. Salt will enter the egg through the pores of the eggshell to the egg white, then to the egg yolk. The salt will draw out the water contained in the egg. through socialization activities on Making Salted Eggs with Water Media to Improve the Soft Skills of Pindrikan Lor Semarang Residents resulting in an understanding of making salted eggs with water media there was a significant increase from 20% to 67%, this shows that the service activities carried out were successful